The Civil Provisions of the Harassment Act 1997 A Worrying Area of Legislation - Mountfort, Jane (Victoria University of Wellington Law Review, 2001)
This article presents a critical analysis of the civil provisions of the Harassment Act 1997 and the leading cases interpreting and applying it. In it, the author suggests that, as currently interpreted by the courts, the Act is a potentially oppressive infringement on normal social relations and individual rights in New Zealand. Noting that the purpose of the Act was to remedy a perceived gap in the law relating to stalking, the author questions whether the more innocuous acts of harassment currently being caught by the Act were intended to be so. The article then considers an alternate interpretation of the Act that would require applicants to show a reasonable fear for safety, and other reform options.